A Comparative Study of Grandparents’ and Parents’ Parenting Styles in Shaping the Discipline of Children Aged 4–6 Years - Afrimelya, Dea; Vitaloka, Wulansari (Journal of Islamic Education Students (JIES), 2025)
This study aims to analyze the differences between grandparents’ and parents’ parenting styles in shaping children’s discipline. The shifting caregiving roles in modern families, particularly due to parents’ work responsibilities, often place grandparents as the primary caregivers, leading to generational differences in values and approaches that may influence children’s discipline. This research employed a comparative quantitative approach involving 66 children in Koto Datuk Village. The sample was selected using purposive sampling, and data were collected through questionnaires based on discipline indicators proposed by Baumrind and Santrock. Data analysis was conducted using an Independent Sample t-Test through SPSS version 30. The findings reveal a significant difference between parents’ and grandparents’ parenting styles, where parents’ democratic parenting is more effective in fostering discipline compared to the more permissive approach typically practiced by grandparents. These results emphasize the importance of active parental involvement in childrearing and the need for educational support for grandparents as alternative caregivers in contemporary family settings.